Design Simulation and Experimental Verification of Optimized Savonious Wind Turbine Profile - Paudel, Anuj; Shrestha, Rajendra (Journal of Advanced College of Engineering and Management, 2025)
Nepal holds significant hydropower potential but has yet to fully exploit it, resulting in limited power production capacity. To address this energy gap, Nepal can tap into wind energy, capable of generating up to 3000 MW, with 448 MW currently exploitable. Nepal traditionally favors horizontal axis wind turbines (HAWTs) but has only recently begun exploring vertical axis wind turbines (VAWTs). VAWTs, such as the Savonius design, are preferred for their simplicity and efficiency in low wind speeds and turbulent environments.The report outlines its design using SOLIDWORKS 17, detailing material selection, dimensions, and assembly. Experimental testing showed it achieved 266 rpm, 0.305 Nm torque, and 27.841 ω angular velocity at 6.3 m/s wind speed. Theoretical values at the same speed were 214.9 rpm, 0.377 Nm, and 22.5 ω, with mean absolute errors between experimental and theoretical results at 18.85% for torque and 15% for rotational speed. Suggestions to enhance efficiency include advanced materials such as carbon fiber.